Cálculo de la capacidad de carga y capacidad de acogida turística multicriterio para la reserva biológica El Encenillo, Guasca, Cundinamarca, Colombia (2021)
The main objective of this research is to carry out a comparison between two methodologies to calculate the maximum daily number of visitors that can enter a natural area where tourism is carried out, to establish the strengths and weaknesses of each of them. The biological reserve El Encenillo was selected as a case study. It is located in the municipality of Guasca, department of Cundinamarca - Colombia. The methodologies used were the Tourist Carrying Capacity (CCT), which was formerly widely used, but has now fallen into disuse and is considered to be subjective, and the Multi-criteria Tourism Hosting Calculation, which follows a method based on the weighting of correction factors through the Analytic Hierarchy Process (AHP), applied at 3 levels of consultation: Sui validatio, Scientatis validatio and Societatis validatio, as a mechanism to reduce subjectivity.